Effects of playing position, pitch location, opposition ability and team ability on the technical performance of elite soccer players in different score line states - Redwood-Brown, A. J.; O`Donoghue, P. G.; Nevill, A. M.; Saward, C.; Sunderland, C. (PLOS ONE, 2018)
The purpose of this study was to investigate the effects of playing position, pitch location, team ability and opposition ability on technical performance variables (pass, cross, corner, free kick accuracy) of English Premier League Soccer players in difference score line states. A validated automatic tracking system (Venatrack) was used to code player actions in real time for passing accuracy, cross accuracy, corner accuracy and free kick accuracy. In total 376 of the 380 games played during the 2011-12 English premier League season were recorded, resulting in activity profiles of 570 players and over 35`000 rows of data. These data were analysed using multi-level modelling. Multi-level regression revealed a "u" shaped association between passing accuracy and goal difference (GD) with greater accuracy occurring at extremes of GD e.g., when the score was either positive or negative. The same pattern was seen for corner accuracy away from home e.g., corner accuracy was lowest when the score was close with the lowest accuracy at extremes of GD. Although free kicks were not associated with GD, team ability, playing position and pitch location were found to predict accuracy. No temporal variables were found to predict cross accuracy. A number of score line effects were present across the temporal factors which should be considered by coaches and managers when preparing and selecting teams in order to maximise performance. The current study highlighted the need for more sensitive score line definitions in which to consider score line effects.